Women's experiences of social support during pregnancy: a qualitative systematic review - Mona Al-Mutawtah; Emma Campbell; Hans-Peter Kubis; Mihela Erjavec (BMC, 2023)
Abstract Background Social support during pregnancy can alleviate emotional and physical pressures, improving the well-being of mother and child. Understanding women's lived experiences and perceptions of social support during pregnancy is imperative to better support women. This systematic review explores and synthesises the qualitative research on women's experiences of social support during pregnancy. Methods Databases PubMed, CINAHL, MEDLINE, APA PsycInfo and Scopus were searched with no year limit. Eligible studies included pregnant women or women who were up to one year postpartum and were assessed on their experiences of social support during pregnancy. The data were synthesised using the thematic synthesis approach. Results Fourteen studies were included with data from 571 participating women across ten countries; two studies used focus groups, and 12 used interviews to collect their data. Four main themes were developed ('a variety of emotional support', 'tangible and intangible instrumental support', 'traditional rituals and spiritual support', and 'the all-encompassing natal home'), and six sub-themes ('female network connections', 'care and affection from the husband', 'dissatisfaction with relationships', 'financial support from the husband and family', 'practical support from family and friends', 'health information support'). Conclusions This systematic review sheds light on women's experiences of social support during pregnancy. The results indicate a broad variety of emotional support experienced and valued by pregnant women from different sources. Additionally, women expressed satisfaction and dissatisfaction with tangible and intangible support forms. It was also highlighted that spirituality played an essential role in reducing stress and offering coping mechanisms for some, whereas spirituality increased stress levels for others.